Prediction of survival in patients with oesophageal or junctional cancer receiving neoadjuvant chemoradiotherapy and surgery. Issue 8 (26th April 2016) - Shapiro, J.; van Klaveren, D.; Lagarde, S. M.; Toxopeus, E. L. A.; van der Gaast, A.; Hulshof, M. C. C. M.; Wijnhoven, B. P. L.; van Berge Henegouwen, M. I.; Steyerberg, E. W.; van Lanschot, J. J. B.
Abstract : Background: The value of conventional prognostic factors is unclear in the era of multimodal treatment for oesophageal cancer. This study aimed to quantify the impact of neoadjuvant chemoradiotherapy (nCRT) and surgery on well established prognostic factors, and to develop and validate a prognostic model. Methods: Patients treated with nCRT plus surgery were included. Multivariable Cox modelling was used to identify prognostic factors for overall survival. A prediction model for individual survival was developed using stepwise backward selection. The model was internally validated leading to a nomogram for use in clinical practice. Results: Some 626 patients who underwent nCRT plus surgery were included. In the multivariable model, only pretreatment cN category and ypN category were independent prognostic factors. The final prognostic model included cN, ypT and ypN categories, and had moderate discrimination (c‐index at internal validation 0·63). Conclusion: In patients with oesophageal or oesophagogastric cancer treated with nCRT plus surgery, overall survival can best be estimated using a prediction model based on cN, ypT and ypN categories. Predicted survival according to this model showed only moderate correlation with observed survival, emphasizing the need for new prognostic factors to improve survival prediction. Abstract : Better predictor still needed